2019
DOI: 10.1177/0269094219841590
|View full text |Cite
|
Sign up to set email alerts
|

Broadband and uneven spatial development: The case of Cardiff City-Region

Abstract: The internet and e-connectivity more generally are increasingly held to be an important element of business success. Evidence however suggests that the productive impacts of such technologies are contingent on factors that include firm size and sector, and human capital. It follows that if companies with these characteristics are unevenly distributed across space, the increasing importance of broadband in economic activity might impact unevenly on economic outcomes across space. We examine the Cardiff City-Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 73 publications
(119 reference statements)
0
16
0
Order By: Relevance
“…It will be smarter, but not as smart as cities. (Transport consultant)Uneven tele-communications infrastructure leads to inequalities in digital skills and uptake among local populations, which is further compounded by the inability of poorer connected areas to attract digitally skilled people or firms (Jones and Henderson, 2019). The Covid-19 lockdown has seen a rapid uptake of telecommunications technologies across all sectors of society but it has also highlighted the challenges for those, typically older, groups of people without to skills or confidence to use mobile or web-based communications.…”
Section: Mobility Innovations and Their Potential For Addressing Ruramentioning
confidence: 99%
“…It will be smarter, but not as smart as cities. (Transport consultant)Uneven tele-communications infrastructure leads to inequalities in digital skills and uptake among local populations, which is further compounded by the inability of poorer connected areas to attract digitally skilled people or firms (Jones and Henderson, 2019). The Covid-19 lockdown has seen a rapid uptake of telecommunications technologies across all sectors of society but it has also highlighted the challenges for those, typically older, groups of people without to skills or confidence to use mobile or web-based communications.…”
Section: Mobility Innovations and Their Potential For Addressing Ruramentioning
confidence: 99%
“…There is also evidence of the impact of SME adoption in terms of increased turnover, employment and innovation benefits ( Henderson et al, 2018 ). The adoption, however, has not been universal, with research finding that firms and sectors in different parts of Wales have benefitted unevenly from these developments ( Jones & Henderson, 2019 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The variables of physical geography were mainly dependent on the natural background environmental conditions, related to geographical location and formed naturally; the economic variables were related to economic income and industrial development; the societal variables were related to social and historical development, influenced by human beings and driven by human development needs. This categorization and choice of variables reflect common practice among researchers working on related studies [19][20][21][22][23][24][25]28,36].…”
Section: Datamentioning
confidence: 99%
“…Natural resources [20], economic [21], infrastructure, and population [22] are commonly considered to be the driving forces in research on the regional urban spatial imbalance. Jones and Henderson [23] demonstrated that the distribution of emerging industries would further expand the gap of urban spatial expansion size between the relatively prosperous coastal zone and the industrial hinterland in the Cardiff City-Region in South Wales. Farmer [24] studied Chicago, USA, and demonstrated that the level of regional infrastructure service, especially public transportation facilities, led to the uneven development of urban spatial development intensity.…”
Section: Introductionmentioning
confidence: 99%